Fitness Profile of Police Officers from Rapid Intervention Teams of the Lisbon Metropolitan Command - João Daniel Freitas; Luís Miguel Massuça (Journal of Functional Morphology and Kinesiology)
Background: A rapid intervention team is a broad category of special teams used by police and emergency respondents to cover various needs. It is essential to ensure the safety and well-being of people in emergencies, minimising the risk of harm and maximising the chances of survival. Objective: This study aimed (i) to identify the fitness profiles and levels of POs from the EIR of the Lisbon Metropolitan Command (COMETLIS, PSP, Portugal), considering age classes; (ii) to directly compare the observed fitness profiles to previous research and normative data; and (iii) to compare the fitness profile of POs from the EIR with cadets from the Police Academy. Methods: This cross-sectional observational study included the participation of 121 male POs from the EIR of the Lisbon Metropolitan Command (Portugal) and 92 male cadets from the Police Academy (Lisbon, Portugal). The assessment protocol sequence involved the collection of biosocial data (age classes: ≤29 years; 30–39 years; 40–49 years), a body size assessment, and a fitness assessment (horizontal jump, handgrip strength, 60 s sit-ups and 20 m shuttle run). Results: (i) In the ≤29 years age class, POs performed better in all fitness tests (highlighting that the age class had a statistically significant effect on performance in the horizontal jump, sit-ups, 20 m shuttle run, and predicted VO2max), and they showed significantly better performance than cadets in handgrip (left, right, and sum), and significantly worse performance in sit-ups and predicted VO2max. (ii) In the 30–39 years age class, POs had significantly worse performance than cadets in the horizontal jump, sit-ups, 20 m shuttle run, and predicted VO2max, even after controlling for age. Conclusions: (i) The fitness performance decreased as the age class became older; (ii) the handgrip strength and cardiovascular capacity attributes were between the standard and excellent levels according to the ACSM guidelines for the general population; (iii) POs from the EIR were stronger than cadets in terms of handgrip strength but weaker in terms of lower limb power, abdominal muscular endurance, and aerobic capacity; and (iv) the differences observed between POs from the EIR and cadets in the 30–39 years age class emphasise the importance of physical training after the training period and throughout professional life.